Pengaruh Persentase Katalis Zeolit Alam terhadap Karakteristik Minyak Hasil Pirolisis Campuran PP-LDPE - Mochammad Mashud Okta Kusuma; Mokh Hairul Bahri; Asroful Abidin (Lembaga Pengembangan Kinerja Dosen, 2026)
Natural zeolite is a crystalline aluminosilicate mineral that has pores and is often used as a catalyst in the pyrolysis process of plastic waste. Zeolite consists of a three-dimensional framework formed by SiO4 and AlO4 tetrahedrons, creating a distinctive microporous pore network with a large surface area and high adsorption capacity. This study aims to determine the effect of the percentage of natural zeolite catalyst on the combustion rate and oil density of the pyrolysis results of PP-LDPE pure mixture. This study is experimental and the process uses catalytic pyrolysis with natural zeolite catalyst in four different percentages, namely 0% (as a control), 5%, 10%, and 15% of the total mass of plastic input, where each experiment uses 3 kg of plastic as the main material. The study was conducted by heating PP and LDPE samples at a temperature of 250°C in the absence of oxygen for 120 minutes. The results of this study indicate that there is a volume variation in each catalyst mixture, indicating that increasing the pyrolysis catalyst has a positive effect on the amount of liquid fraction produced. A 15% natural zeolite catalyst yielded a maximum yield of 576 ml, equivalent to a 650% increase compared to pyrolysis without a catalyst (0%).